2016
DOI: 10.2196/mededu.5606
|View full text |Cite
|
Sign up to set email alerts
|

Health Sciences Students’ Self-Assessment of Information and Communication Technology Skills and Attitude Toward e-Learning

Abstract: BackgroundIn medical education, information and communication technology (ICT) knowledge and skills have become a necessity and an integral part of preparing tomorrow’s doctors to be sufficiently competent to use informatics resources effectively and efficiently for the best practice of medicine.ObjectiveThis research aimed to study the literacy of the preprofessional students in ICT before and after taking the basic informatics course at the Health Sciences Center at Kuwait University, to understand their pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
1
11
0
1
Order By: Relevance
“…Mohammed et al ( 14 ) discovered that only 33.7% of the health care workers had adequate computer knowledge. In a research carried out by Buabbas et al, the self-assessed results of students showed that initially, their level of HIT knowledge was low and only 9.29% of them have used computers professionally ( 21 ). In contrast to our findings, Gour and Srivastava ( 15 ) reported that 57.91% of health care professionals had knowledge about computers.. A study by Baraka et al declared that 80.9% of participants had full or almost full training for using the Internet and IT applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohammed et al ( 14 ) discovered that only 33.7% of the health care workers had adequate computer knowledge. In a research carried out by Buabbas et al, the self-assessed results of students showed that initially, their level of HIT knowledge was low and only 9.29% of them have used computers professionally ( 21 ). In contrast to our findings, Gour and Srivastava ( 15 ) reported that 57.91% of health care professionals had knowledge about computers.. A study by Baraka et al declared that 80.9% of participants had full or almost full training for using the Internet and IT applications.…”
Section: Discussionmentioning
confidence: 99%
“…In a case in 2015, Baraka et al assessed the acceptance and knowledge of IT in health care practice ( 19 ), while Sinha and Shetty studied the attitude of physicians towards the efficiency of HIT in Ayurveda educational hospital ( 20 ). Another study was done by Buabbas et al in 2016 entitled “Health Sciences Students’ Self-Assessment of Information and Communication Technology Skills and Attitude Toward e-Learning” ( 21 ). Manganello et al also assessed the relation of health knowledge and using IT ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of all education systems is to improve the learning process, and educators need to know the educational strategies, methods and procedures, as well as the ways in which students learn. New technological developments are reflected directly in the educational system, and the way of their application and implementation depends on informatics and communication technologies [23,36]. As the communication technologies are inevitable in all spheres of life and work, all students should be well prepared to apply informatics technologies in the future workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Desde el año 2000 con la globalización, se ha incrementado la oferta de cursos en línea y aulas virtuales, las cuales utilizan una variedad de herramientas multimedia que pueden fomentar estrategias educativas que mejoren o se adapten al aprendizaje individual (Moore, 2011;Buabbas, 2016). En 2005 con el desarrollo de la web 2.0, se abrieron nuevas dimensiones en el aprendizaje en línea que permite la participación interactiva y colaborativa con las plataformas virtuales (Vervaart, 2012).…”
Section: Introductionunclassified